The coordination channel of foreign exchange intervention: a nonlinear microstructural analysis - Stefan Reitz; Mark P. Taylor (Deutsche Bundesbank, 2006)
The coordination channel has been proposed as a means by which foreign exchange market intervention may be effective, in addition to the traditional portfolio balance and signaling channels. If strong and persistent misalignments of the exchange rate are caused by non-fundamental influences, such that a return to equilibrium is hampered by a coordination failure among fundamentals-based traders, then central bank intervention may act as a coordinating signal, encouraging stabilizing speculators to re-enter the market at the same time. We develop this idea in the framework of a simple microstructural model of exchange rate movements, which we then estimate using daily data on the dollar-mark exchange rate and on Federal Reserve and Bundesbank intervention operations. The results are supportive of the existence of a coordination channel of intervention effectiveness.
Keywords: C10; F41; F31; 330; foreign exchange intervention; coordination channel; market microstructure; nonlinear mean reversion; Wechselkurspolitik; Internationale wirtschaftspolitische Koordination; Devisenspekulation; Devisenmarkt; Mikrostrukturanalyse; Schätzung; Theorie; Deutschland; USA